Proposed upgrading to the existing interior design of Nineteen81 Rest House Tapah at Bukit Rumah Rehat Jalan Stesyen, 35000,Tapah,Perak for For Le Shuttle Event Sdn.Bhd / Wan Suhaili Wan Dris - Wan Dris, Wan Suhaili (Faculty of Architecture, Planning and Surveying, 2012)
The title of final project is Proposed upgrading interior design of Nineteen81 Rest House Tapah for Le Shuttle Shuttle Event Sdn.Bhd.at Bukit Rumah Rehat,Jalan Stesyen ,3500 Tapah Perak Darul Ridzuan.The nineteen81 rest house Tapah is strategically located close to major shopping ,sightseeing and business destination. I have choosen Mr.Zamari Bin Hj.Muhyi general manager at nineteen81 as my client. All the data and information gathered throughout the process will be used as a design guideline to come with a design that could fulfill client, worker and the end user needs. Therefore, a thorough planning on the space and a suitable concept that I have choose to implement on this project to give nineteen81 more interesting place that can attract more customer come to the rest house Tapah.